Caffeine decreases systemic urea in elite soccer players during intermittent exercise - Bassini, A.; Magalhaes-Neto, A. M.; Sweet, E.; Bottino, A.; Veiga, C.; Tozzi, M. B.; Pickard, M. B.; Cameron, L. C. (Medicine & Science in Sports & Exercise, 2013)
Purpose: We investigated the effects of caffeine on the ammonia and amino acid metabolism of elite soccer players.